Original paper Expression of selected pro-apoptotic proteins in pemphigoid - Erkiert-Polguj, Anna; Żebrowska, Agnieszka; Wągrowska-Danilewicz, Małgorzata; Danilewicz, Marian; Nykiel, Anna; Waszczykowska, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Bullous pemphigoid (BP) is the most common blistering disease, developing especially among people over the age of 70. Apoptosis, also known as programmed cell death, seems to be involved in many inflammatory and malignant skin diseases. Aim : Because of the scarcity of data concerning the role of apoptosis in BP, the study was aimed at analyzing pro-apoptotic factors (Bax, Fas, FasL, TRAIL and TRAIL-R) in lesional and perilesional skin using immunohistochemical methods. Material and methods : The study was performed on 22 patients with bullous pemphigoid before treatment. Ten healthy volunteers, selected according to their sex and age, made up the control group. Results : Bax protein expression was revealed in the cytoplasm of keratinocytes in samples of lesional skin, weaker in perilesional skin and the weakest in samples taken from healthy volunteers. Immunostaining of Fas in lesional skin was detected in the cytoplasm of keratinocytes, less intense in perilesional skin. Fas ligand expression was discovered in the basal layer of the epidermis and inflammatory infiltrates. None of the samples taken from healthy participants revealed Fas or Fas ligand expression. Immunostaining of TRAIL was detected in the cytoplasm of keratinocytes as well as in inflammatory cells and some fibroblasts in lesional skin. In perilesional skin and in healthy skin the expression was observed in keratinocytes and some fibroblasts, and it was less intense. Immunostaining of TRAIL receptor was revealed in inflammatory infiltration, in the cytoplasm of keratinocytes as well as in some fibroblasts in lesional skin, in perilesional skin and in healthy skin. The expression of TRAIL-R was more intense in perilesional than in lesional skin. Conclusions: The more intense expression of TRAIL receptor DR4 on keratinocytes and cells of inflammatory infiltration in perilesional than in lesional skin may imply its role in maintaining the inflammatory process and damage to the dermo-epidermal junction. It is difficult to evaluate clearly the role of proteins in BP pathogenesis because they take part both in mechanisms of apoptosis and inflammatory process intensification.